Analysis of River Environmental Pollution Factors - Erpita Yanti; Yessy Aprihatin; Armaita (Jurnal Penelitian Pendidikan IPA, 2024)
The problem of polluted river water quality is part of current environmental problems. A lot of pollution is caused by industrial factory waste, household waste, and rubbish. This causes the condition of the river ecosystem to decline and hurts humans and the environment. Pollution that occurs in rivers is a result of human behavior which increasingly ignores the surrounding environment. The consequences of human behavior that is wrong in treating the river environment will ultimately become a disaster that is detrimental to humans themselves. This research aims to detect whether there is a correlation between knowledge and attitudes held by the community regarding behavior to protect the river environment. The hypothesis proposed in this study is: that behavior to maintain the health of the river environment is influenced by knowledge and attitude variables. The sample in this research was 300 students. The influence of knowledge on behavior has a significant relationship with a p-value of 0.00. The influence of attitudes on behavior has a significant relationship with a p-value of 0.00. There is positive behavior to protect river ecosystems and also environmental sustainability in rivers, but there are also students who behave indifferently towards the environment and tend to be indifferent.